The Adaptation Dynamics of Agritourism Destination: A Case Study of Ban Sala Din Community, Mahasawat Canal, Phutthamonthon District, Nakhon Pathom Province - Katpiyarat, Piyapong (Journal of Business, Innovation and Sustainability (JBIS), 2022)
This qualitative research aims to investigate the adaptation dynamics of agritourism destination: a case study of Baan Sala Din community. Klong Maha Sawat, Phutthamonthon District, Nakhon Pathom Province. It is collected data by; 1) Document analysis 2) In-depth interview with 4 formal leaders, 6 informal leaders, 10 tourist shop operators, 20 residents, using a continuous referral technique and 20 tourists who travel to Khlong Maha Sawat community by accident sampling and 3) data collection by focus group. The findings of this study are summarized as follows: 1) in 1859-1977, the area began to dig the canal and there were not crowded population. People work in agriculture sector 2) in 1977-1997, it is naturally a canal trade life-style 3) in 1997-present, community has transformed to agritourism destination.It has affected increasing in household income of the community. On the other hand, It has an impact on community life-style and has environmental problem issues.